2001
DOI: 10.1002/cm.10002
|View full text |Cite
|
Sign up to set email alerts
|

Saturable binding of the echinoderm microtubule‐associated protein (EMAP) on microtubules, but not filamentous actin or vimentin filaments

Abstract: The echinoderm microtubule-associated protein (EMAP) is a 75-kDa, WD-repeat protein associated with the mitotic spindle apparatus. To understand EMAP's biological role, it is important to determine its affinity for microtubules (MTs) and other cytoskeletal components. To accomplish this goal, we utilized a low-cost, bubble-column bioreactor to express EMAP as a hexahistidine fusion (6his) protein in baculovirus-infected insect cells. After optimizing cell growth conditions, up to 30 mg of EMAP was obtained in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…All EMAP-like proteins are characterized as having a Hydrophobic ELP (HELP) domain/motif and a WD domain (Eichenmuller et al, 2002). The HELP domain is required for microtubule binding and it is assumed that the WD repeat domain is required for additional protein-protein interactions (Eichenmuller et al, 2001; Tegha-Dunghu et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…All EMAP-like proteins are characterized as having a Hydrophobic ELP (HELP) domain/motif and a WD domain (Eichenmuller et al, 2002). The HELP domain is required for microtubule binding and it is assumed that the WD repeat domain is required for additional protein-protein interactions (Eichenmuller et al, 2001; Tegha-Dunghu et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, MT-bound Myo5a retains its characteristic ATPdependent interactions with F-actin without dissociating from the MT as demonstrated by cosedimentation analysis (Figure 4) and the ATP-dependent dissociation of MTMyo5a-actin gels under low Ca 2ϩ conditions (Figures 3 and 4), and contraction of these gels into aster-like arrays in the presence of Ca 2ϩ (Figures 7-9) . The interaction of native Myo5a with MTs is saturable and occurs with high affinity, suggesting that Myo5a is a bona fide MAP and that MTs should be added to the ever-grow-ing list of cargos for this myosin (reviewed in Reck-Peterson et al, 2000;Karcher et al, 2002;Langford, 2002 Eichenmuller et al, 2001]). However, at saturation the ratio of Myo5a:tubulin is relatively low (1:22-24) compared with other MAPs such as (Pedrotti and Islam, 1994) MAP2 (1:12) (Burns and Islam, 1984), or XMAP215 (1:16) (Gard and Kirschner, 1987) that bind substoichiometrically to tubulin dimers in the MT.…”
Section: Discussionmentioning
confidence: 99%
“…This high degree of conservation among ELP family members indicates that the HELP domain is likely to be critical to ELP function. For example, a preliminary study has shown that the NH 2 terminus of sea urchin EMAP, which contains the HELP domain, is sufficient for MT binding in vitro (43).…”
Section: Conservation Of a Hydrophobic Emap-like Protein (Help)mentioning
confidence: 99%